An analysis of investment efficiency - Durczok, Maciej; Machek, Ondřej, 1985-; Kopkáně, Heřman; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor thesis aims to evaluate the efficiency of an investment – the acquisition of a farm. The theoretical part consists of fundamental investment principles, such as the time value of money and the discount rate estimation. Afterward, the thesis deals with various investment appraisal methods including return on investment, payback period, net present value, and modified internal rate of return. Sensitivity and risk analysis is also conducted to estimate the investment decision's longevity and strength. The practical part of the thesis is evaluating the investment while considering suitable financing option. The thesis summarizes the findings and answers the questions concerning efficiency and potential risks associated with the investment project.
Vedoucí práce: Ondřej Machek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses